"Pesawat Kertas", a Game that Motivates Students in Learning Bahasa Indonesia - Santoso, Sugeng (International Journal Education and Computer Studies (IJECS), 2022)
Online learning implemented in Indonesia caused many negative impacts, such as decreased student motivation and the creation of loss of learning. One way to overcome this is through the implementation of learning while playing. This research aims to describe the pesawat kertas (paper plane) game in learning Bahasa Indonesia in VII-A class, SMP Hamparan 2. The research method used is descriptive qualitative. The data in this research were obtained from documentation and questionnaires. The data analysis technique used is Miles and Huberman model. The results of this research indicate that the preparation of the pesawat kertas game in learning Bahasa Indonesia for VII-A class, SMP Hamparan 2 has been done very well. The stages in the preparation of learning are: analyze the syllabus, choosing learning media, making evaluation tools, making learning plans, and compiling the concept of the game that is carried out. Second, the stages and plots of the pesawat kertas game are pretty good and coherent. Readers can also see videos of students' excitement on Instagram of SMP Hamparan 2. The response of subjects to the pesawat kertas game that has been done is excellent. This can be seen from as many as 90% subjects agreeing that the game is fun and can make the spirit of learning.